Comparison of Strength and Durability in Properties of Concrete with Partial Replacement of Ground Granulated Blast Furnace Slag A Review - Sheetal Kumar; Bhojram (International Journal of Scientific Research in Civil Engineering, 2024)
Concrete is defined as the mixture of sand (FA) , Gravel (CA) and Water. it plays a very important role in the infrastructure development. the utilized material 2 of supplementary cementation should be accepted , since it give several properties in the concrete as well as economy. this paper present an investigation on the study of the effect of GGBFS On strength development of mortar and the optimum use of slag in mortar .Cement was partially replaced with seven percentage (40%, 42%, 44%, 46%,48%,50%) of slag by weight . to analysis all about fineness test of cement, sieve analysis, specific gravity test. Determination of specific surface (total surface area of all the particles in one gram of cement) by air-permeability apparatus used to test fineness. Fineness modulus is an empirical factor obtained by adding the cumulative percentages of fine aggregate which retained on each of the standard sieves ranging from 4.75 mm to 150 micron and dividing this.